A modelling and simulation framework for compound medical applications in regional healthcare networks. (4th April 2005) - Kormentzas, George; Maglogiannis, Ilias; Vassis, Dimitris; Vergados, Dimitris; , Angelos Rouskas
Regional healthcare information networks have already started to grow across Europe, in order to cover local healthcare provision needs, especially in isolated regions, where there is often no availability of central general hospitals. The paper discusses a modelling and simulation framework for the design of regional healthcare information networks running compound medical and QoS–sensitive applications. The proposed framework decomposes the compound medical applications into combinations of elementary traffic profiles, assesses appropriate values to the traffic parameters of the assigned models and defines suitable simulation scenarios. The simulation results are analysed and finally lead to reliable bandwidth estimations of the links of the healthcare information network under design. The proposed framework has been thoroughly validated through its application for the design of a healthcare network in the islands of the North Aegean Sea, running actual compound medical applications in the context of a national research project.